To find the linear function equation for the arithmetic sequence given by \( a_n = 13 + (n-1)(-2) \), we can simplify this expression.
-
Start with the given equation: \[ a_n = 13 + (n-1)(-2) \]
-
Distribute \(-2\): \[ a_n = 13 - 2(n-1) = 13 - 2n + 2 \]
-
Combine like terms: \[ a_n = 15 - 2n \]
This can be rewritten as: \[ a_n = -2n + 15 \]
Now, to express it in the form \( y = mx + b \), we can identify \( m = -2 \) and \( b = 15 \).
Thus, the linear function equation is: \[ y = -2x + 15 \]
So, the correct response is: y = -2x + 15.